Hubungan Pengetahuan Ibu Hamil Dengan Implementasi P4K Di Wilayah Kerja Puskesmas Sitiung II Kecamatan Koto Salak Kabupaten Dharmasraya Tahun 2023 - Selvira, Aisyah; Khotimah, Siti; Husna, Husna (Bunda Edu-Midwifery Journal (BEMJ), 2023)
P4K is a program launched in an effort to accelerate the reduction in maternal mortality. 2021 is the year with the highest number of maternal deaths in the last 5 years. Meanwhile, in 2022 the MMR has decreased to 6 mothers including maternal deaths caused by bleeding, eclampsia, and tuberculosis, and these causes can be prevented by using P4K. This study aims to determine the relationship between knowledge and attitudes of pregnant women with the implementation of the Birth Planning and Complication Prevention Program (P4K) in the work area of ​​the Sitiung II Health Center, Dharmasraya Regency. This research is descriptive analytical research. The research design uses a cross sectional research design, the sample taken is total sampling where all members of the population are used as samples with a research instrument using a questionnaire. The results of this study showed that there was no relationship between the knowledge of pregnant women and the implementation of P4K with a P value equal to 0.294 (P value more than 0.05), there was a relationship between the attitudes of pregnant women and the implementation of P4K with a P value equal to 0.037 (P value less than 0.05) . It was concluded that the knowledge of pregnant women had nothing to do with the implementation of P4K, while the attitudes of pregnant women had a relationship with the implementation of P4K. It is recommended that health institutions or village midwives provide education about implementing P4K properly and correctly